Anxiety and posttraumatic stress in post-acute sequelae of COVID-19: prevalence, characteristics, comorbidity, and clinical correlates - Ferrando, Stephen J.; Lynch, Sean; Ferrando, Nicole; Dornbush, Rhea; Shahar, Sivan; Klepacz, Lidia (Frontiers in Psychiatry, 2023)
Background Anxiety and post-traumatic stress symptoms have been reported in association with acute and post-acute sequelae of COVID-19 (PASC). Purpose This study aimed to document the cross-sectional prevalence, characteristics and clinical correlates of anxiety and post-traumatic stress in a study of neuropsychiatric sequelae of COVID-19. Method 75 participants recruited from a post-COVID-19 recovery program and the community were assessed for sociodemographic, medical, psychiatric, and neurocognitive symptoms and performance. The generalized anxiety questionnaire-7 (GAD-7) and post-traumatic stress disorder questionnaire for DSM5 (PCL5) were utilized to measure anxiety and PTSD symptoms. Established cutoff scoring for the GAD-7 and algorithm-based scoring of the PCL5 were utilized to determine clinically significant anxiety symptoms and PTSD, respectively. Results The cohort was 71% female, 36% ethnic minority, with the main age of 43.5 years, 80% employment, 40% with the prior psychiatric treatment history and 2/3 seeking post-COVID care for PASC. Clinically significant anxiety symptoms were found in 31% and PTSD was found in 29% of the cohort. Nervousness and excessive worry were the most prominent anxiety symptoms, while changes in mood/cognition and avoidance were most frequent in PTSD. There was a high degree of comorbidity between clinically significant anxiety symptoms, PTSD, depression and fatigue. In logistic regression, acute COVID illness severity, prior psychiatric history, and memory complaints (but not objective neuropsychological performance) predicted clinically significant anxiety symptoms and/or PTSD. Conclusion Clinically significant anxiety and PTSD are found in approximately 1 of 3 individuals after COVID-19 infection. They are highly comorbid with each other as well as with depression and fatigue. All patients seeking care for PASC should be screened for these neuropsychiatric complications. Symptoms of worry, nervousness, subjective changes in mood, and cognition as well as behavioral avoidance are particularly important targets of clinical intervention.